RESPONSE OF SEMI-SUBMERSIBLE PLATFORM BY MORISON EQUATION AND DIFFRACTION THEORY - Kurian, V.J. (2010)
ABSTRACT This paper presents the dynamic motion responses of an offshore semi-submersible platform in regular sea waves obtained by applying numerical time domain dynamic integration using Morison equation in the first case and diffraction theory in the second case. The platform was modeled as a rigid body with three degrees of freedom restrained by mooring lines. Linear Airy wave theory and Morison modified equation were used for calculating the wave forces on the platform in the first case. The mass, damping and stiffness matrices were evaluated at every time step and the equations of motion were formulated for the platform dynamic equilibrium. Newmark Beta time domain integration method was implemented to solve the equations of motion. The results were obtained as response amplitude operator (RAO) in surge, heave and pitch. In the second case, the RAOs were obtained using a software based on linear wave diffraction method. The results were compared and conclusions arrived at. The diffraction results gave significantly higher responses compared to the Morison responses in the surge, heave and pitch degrees of freedom. Keywords: Semi submersible platforms, Hydrodynamic analysis, Degree of freedom (DOF), Morison modified equations, Diffraction theory, and Response amplitude operator (RAO).